Bi(OAc)3/chiral phosphoric acid catalyzed enantioselective allylation of isatins. Issue 2 (6th December 2019) - Wang, Jie; Zhang, Qingxia; Li, Yao; Liu, Xiangshuai; Li, Xin; Cheng, Jin-Pei
Abstract : Herein, we disclosed an efficient protocol for the construction of chiral 3-allyl-3-hydroxyoxindoles via the enantioselective allylation reaction of isatins and allylboronates catalyzed by a simple binary acid Bi(OAc)3 /CPA system under mild conditions. Abstract : Herein, we disclosed an efficient protocol for the construction of chiral 3-allyl-3-hydroxyoxindoles via the enantioselective allylation reaction of isatins and allylboronates catalyzed by a simple binary acid Bi(OAc)3 /CPA system under mild conditions. The synthetic utility of this strategy has been demonstrated through the formal synthesis of ent -CPC-1.